PHENOTYPIC AND BEHAVIOURAL TRAITS OF SOME ECO-RACES OF TASAR SILKWORMS UNDER THE EFFECTS OF DIFFERENT ENVIRONMENTAL CONDITIONS - NITU KUMARI; S. P. ROY (The Bioscan, 2011)
The paper records information on phenotypic and behavioural traits of eco-races of tasar silkworms. There are 44 eco-races of tropical tasar silk reported from 17 states of India. But 6 eco-races of tasar silkworms are most commonly found. These races are Sarihan, Daba, Jata–Daba, Sukinda and Modal respectively. The differentiation of these races depends upon the environmental factors such as temperature, humidity, rainfall, altitude, photoperiod which have great impact on the biology and voltinism of silkworms. The ambient environmental conditions are such physical factors as temperature, humidity, photoperiod and rainfall. The temperature (24±2 to 28±2ºC), relative humidity (74±2 to 88±2%), photoperiod (100–242 hr per month) with (11-12.50 hours), day length, rainfall (230±1 to 260±1 mm) was found successful for developing better yield of life cycle, fecundity, cocoon and absolute silk filament length of tasar silkworms. The eco-races of Sarihan (25ºC), Daba (29ºC), Jata Daba (30ºC) were reared on normal temperature but Sukinda (25ºC) and Modal (32ºC) in lowest and highest temperature respectively. The relative humidity for the success of the eco-races of Sarihan, Daba, Jata–Daba, Sukinda and Modal were recorded as 80, 82, 85, 75 and 90% respectively. Daba race has maximum reliability among all the eco-races. The eco-races Sarihan and Daba are more productive under present environmental conditions and on the view of reelability more beneficial under large scale exploitation for their commercialization as a cottage industry for its sustainable development.